Clostridium difficile Infection Following Spine Surgery: Incidence, Risk Factors, and Association With Preoperative Antibiotic Use. Issue 22 (15th November 2020) - Bell, Joshua; Vatani, Jasmine; Raad, Micheal; Labaran, Lawal; Puvanesarajah, Varun; Hassanzadeh, Hamid
Abstract : Study Design: Retrospective database review. Objective: The aim of this study was to determine the incidence of Clostridium difficile infection (CDI) within 90 days following elective spine surgery; examine risk factors associated with its development; and evaluate the impact of CDI on postoperative outcomes. Summary of Background Data: Although previous studies provided valuable insight into the rate of CDI following spine surgery and associated risk factors, to date no study has evaluated the role preoperative antibiotics use plays in the development of CDI, as well as its impact on 90-day outcomes. Methods: A retrospective database review of Humana patients ages 20 to 84 years who underwent elective spine surgery between 2008 and 2016 was conducted. Following exclusion criteria, the population was divided into patients who developed CDI within 90 days of surgery and those who did not. All risk factors and outcomes were analyzed using multivariate regression. Results: A total of 63, 667 patients met study criteria. Ninety-day incidence of CDI was 0.68%. Notable medical risk factors ( P  < 0.05) included preoperative fluoroquinolone use (odds ratio [OR] 1.40), advanced age (OR 1.86), chronic kidney disease stage I/II (OR 1.76) and III-V (OR 1.98), decompensated chronic liver disease (OR 3.68), and hypoalbuminemia (OR 3.15). Combined anterior-posterior cervical (OR 2.74) and combined anterior-posterior lumbar (OR 2.43) approaches and procedures spanning more than eight levels (OR 3.99) were associated with the highest surgical risk ( P  < 0.05) of CDI. CDI was associated with a 12.77-day increase in length of stay ( P  < 0.05) and increased risk of readmission (OR 6.08, P  < 0.05) and mortality (OR 8.94, P  < 0.05). Conclusion: Following elective spine surgery, CDI increases risk of readmission and mortality. In addition to preoperative fluoroquinolone use, novel risk factors associated with the highest risk of CDI included decompensated chronic liver disease, posterior approaches, and multilevel involvement. Perioperative optimization of modifiable risk factors may help to prevent occurrence of CDI. Level of Evidence: 3 Abstract : Supplemental Digital Content is available in the textRetrospective review of 63, 667 elective spine patients found the 90-day incidence of Clostridium difficile infection to be 0.68%. Notable risk factors included preoperative fluoroquinolone use, advanced age, chronic kidney disease, decompensated chronic liver disease, hypoalbuminemia, combined anterior-posterior approaches, and multilevel involvement. Affected patients had higher risk of mortality and readmission.